Phytochemical Analysis, Antioxidant, and Acetylcholinesterase Inhibitory Activity of Propolis from Northeastern Algeria - Ouahab, A; Grara, N; Menaiaia, K; Khaldi, F; Bensouic, Ci (My University, 2022)
Propolis is a bee resinous substance consisting mainly of phenolic compounds having nutritional and therapeutic properties and formed by the mixing of the tree and plant secretions collected by honey bees. Herein, the present study was aimed to assess the antioxidant and anticholinesterase activity of ethanolic and acetone propolis extracts from two sampling sites in Souk Ahras city (northeast Algeria). The antioxidant activity of the extracts was determined by using the common antioxidant assays (1,1- diphenyl-2-picrylhydrazyl [DPPH], acide 2-2’-azino-bis (3- ethylbenzothiazoline-6-sulphonique) [ABTS], galvinoxyl radical [GOR], and cupric reducing antioxidant capacity [CUPRAC]), and the anticholinesterase activity was determined against acetylcholinesterase (AChE). Moreover, the total phenolic (TPC), flavonoid (TFC), and condensed tannins (CTC) contents were quantified. The propolis extracts showed a potent antioxidant/inhibitory activity which almost met that of synthetic antioxidants used as standards (butylated hydroxytoluene [BHT] and butylated hydroxyanisole [BHA]). In addition, the AChE activity was highly strongly inhibited in a dose-dependent manner by the propolis extracts. The propolis extracts proved their richness in bioactive molecules able to enhance various biological activities